Portable Electronic Devices: Interference in navigation and communication systems of aircrafts - Santos, João Pedro de França; Santos, Roberto Márcio (Law, State and Telecommunications Review, 2017)
Purpose ”“ To analyze interferences on navigation and communication systems caused by portable electronic devices. Methodology ”“ This article tackles the operation method of the portable electronic device, exploratory research of Brazil’s regulation and other countries, as well as lists instruments that can be under the effect of those interferences. Findings ”“ Interferences exist and they can be avoided. Each country has its usage rules and those responsible for allowing and supervise the use of these devices onboard aircraft. Practical implications ”“ The findings show us the different ways of regulating worldwide the same portable electronic devices.